PARENTING STYLES AND PERSUADABILITY AMONG CHILDREN IN CONFLICT WITH THE LAW - Cabrera, Ezra Jed P. Forteza, Carell L. Pe Jennifer M. Rosales, Reuell Christian D. 4 0 16; 5 (2012)
ABSTRACT The present study examined how different parenting styles and persuadability affect the growth of children. Fifty children sentenced with robbery case were used as respondents in the study, they are asked to answer a two part questionnaire to identify what parenting style is used on them and also to know the level of their persuadability. The results indicated that neglectful parenting style is the most dominant parenting style used among children in conflict with the law, and that permissive parenting style was the least dominant parenting style used among children in conflict with the law. This research suggests that other fields aside from persuadability are to be used as another variable.
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila 2012.;College of Human Development Psychology.
Keywords: 2 -- 0; 6; 20; 20; 2